A novel approach to the structural distortions of U/Th snub-disphenoids and their control on zircon → reidite type phase transitions of U1−xThxSiO4. (7th January 2020) - Mondal, Sudip Kumar; Das, Pratik Kr; Mandal, Nibir; Arya, Ashok
Abstract: Coffinite (USiO4 ) and thorite (ThSiO4 ) are conspicuous radiogenic silicates in the geonomy. They form U1− x Th x SiO4 (uranothorite) solid solutions in zircon-type phase. Investigating the phase-evolution of these minerals is of utmost significance in realizing their applicability in the front-as well as at the back-end of nuclear industries. We carried out a systematic study of zircon- to reidite-type (tetragonal I41 /amd to I41 /a) structural transitions of U1− x Th x SiO4 solid solution, and investigated their mechanical behaviour. We found a unique behaviour of transition pressure with the change in U-Th concentration in the solid solution. The phase transition pressure ( p  t ) is found to be minimum for x   =  0.5. We develop the necessary formalism and present an efficient method to estimate the longitudinal and angular distortions of U/ThO8 -triangular dodecahedra (snub-disphenoids). We have parameterized two new factors: δ (longitudinal distortions) and σ 2 (angular distortions) to quantify the polyhedral distortions. A detailed analysis of U/ThO8 snub-disphenoidal distortions is presented to address such variation of p  t with U and Th concentration. We argue that our approach is independent of polyhedral volume and can be used for any AB8 (A: cation, B: anion) type snub-disphenoidal system.